Triple jeopardy for the west aggressive secularism, radical Islamism and multiculturalism - Nazir-Ali, Michael (Bloomsbury Academic, 2012)
Bishop Michael Nazir-Ali considers the impact that aggressive secularism, radical Islamism and multiculturalism are having on the Western world, and particularly Britain